2006
DOI: 10.1007/s11746-006-5014-1
|View full text |Cite
|
Sign up to set email alerts
|

Microwave roasting effects on the physico‐chemical composition and oxidative stability of sunflower seed oil

Abstract: The purpose of the present study was to explore the influences of microwave heating on the composition of sunflower seeds and to extend our knowledge concerning the changes in oxidative stability, distribution of FA, and contents of tocopherols of sunflower seed oil. Microwaved sunflower seeds (Helianthus annuus L.) of two varieties, KL-39 and FH-330, were extracted using n-hexane. Roasting decreased the oil content of the seeds significantly (P < 0.05). The oilseed residue analysis revealed no changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
107
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(134 citation statements)
references
References 34 publications
25
107
1
1
Order By: Relevance
“…The amounts of ash, crude protein, and fibre in MW roasted perah seed samples were found to be almost the same to those of the control sample (Table 1). The present results are in agreement with the results reported by Anjum et al (2006) for sunflower seeds. However, the ash, crude protein and fibre content were in the range of 3.33-3.39%, 29.18-29.33%, and 9.37-9.48% respectively.…”
Section: Changes In Proximate Compositionsupporting
confidence: 94%
“…The amounts of ash, crude protein, and fibre in MW roasted perah seed samples were found to be almost the same to those of the control sample (Table 1). The present results are in agreement with the results reported by Anjum et al (2006) for sunflower seeds. However, the ash, crude protein and fibre content were in the range of 3.33-3.39%, 29.18-29.33%, and 9.37-9.48% respectively.…”
Section: Changes In Proximate Compositionsupporting
confidence: 94%
“…Acid value stayed relatively constant, as can be seen that untreated waste was 2.20% and microwave pretreatment waste was 2.35%. Increment in the acid value of oil may be attributed to hydrolysis of triacylglycerol by microwave to produce more amount free fatty acids [17]. Peroxide value is employed to measure the quantity of peroxides in the oil; these substances are important intermediate product of oxidative reactions since they decompose via transition metal irradiation and due to elevated temperatures to form free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The peroxide value of the oil obtained from the roasted sample increased considerably (about 65% (p < 0.05)) compared to the raw one while the acid value decreased significantly (about 63% (p < 0.05)), (Table 1). With reference to the peroxide value, most studies (Anjum et al, 2006;Vujasinovic et al, 2012) reported a noticeable increase in the peroxide value with increasing roasting temperature and time whereas a few others (Abou-Gharbia et al, 2000) observed only a marginal decrease compared to unroasted samples. Generally, peroxide value does not correspond to the absolute state of oxidation of oil because hydroperoxides become unstable upon heating and decompose to secondary products (Choe and Min, 2006).…”
Section: Physical Properties Of Oil Seeds Of M Peregrinamentioning
confidence: 99%